Residents' support for tourism. An Identity Perspective - Nunkoo, R.; Gursoy, D (2012)
Studies on residents' support for tourism have primarily been conducted in the developed world. This study analyzes community support in the island economy of Mauritius by testing a model based on the social exchange theory and the identity theory. The model proposes that the resource-based occupational identity, environmental identity, and gender identity of the residents influence attitudes to tourism impacts and support (behavior). Results indicate that one's identity has a direct bearing on support, but may not always influence attitudes. Findings confirm the relevance of the social exchange theory and the identity theory in explaining community support for tourism in island economies. The study's practical implications and limitations are discussed. © 2011 Elsevier Ltd.